Transmissions and Translations in Medieval Literary and Material Culture
1 online resource.
Keywords: Bringing together the work of scholars from disparate fields of enquiry, this volume provides a timely and stimulating exploration of the themes of transmission and translation, charting developments, adaptations and exchanges - textual, visual, material and conceptual - that reverberated across the medieval world, within wide-ranging temporal and geographical contexts. Such transactions generated a multiplicity of fusions expressed in diverse and often startling ways - architecturally, textually and through peoples' lived experiences - that informed attitudes of selfhood and 'otherness', senses of belonging and ownership, and concepts of regionality, that have been further embraced in modern and contemporary arenas of political and cultural discourse. Contributors are Tarren Andrews, Edel Bhreathnach, Cher Casey, Katherine Cross, Amanda Doviak, Elisa Foster, Matthias Friedrich, Jane Hawkes, Megan Henvey, Aideen Ireland, Alison Killilea, Ross McIntire, Lesley Milner, John Mitchell, Nino Simonishvili, and Rachael Vause.